"We Make Our Tools and Our Tools Make Us": Lessons from Photographs for the Practice, Politics, and Poetics of Diplomatics - Schwartz, Joan M. (Archivaria, 1995)
In response to Luciana Duranti’s quest for "new uses for an old science," this initial effort to apply diplomatics to photograph in Canadian archives surveys the concepts of diplomatics in the context of photographic form and function. The practice, politics, and poetics of diplomatics are explored and the implications of embracing a positivist tool in a postcustodial, postmodern world are discussed. RÉSUMÉ En réponse à la recherche de Luciana Duranti de «nouveaux usages d’une ancienne science» cet effort initial d’application de la diplomatique à la photographie dans les archives canadiennes, procède à un survol des concepts de diplomatique dans le contexte de la forme et de la fonction photographiques. L’exercice, les politiques et la poétique de la diplomatique sont explorées ainsi que les implications de l’adoption d’un outil «positiviste» dans une période d’archivistique post-moderne.